1998
DOI: 10.1103/physrevc.57.2126
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurement of charge symmetry breaking innpelastic scattering at 347 MeV

Abstract: A nonzero difference of the analyzing powers due to charge symmetry breaking has been measured with high precision in np elastic scattering at a neutron beam energy of 347 MeV. The neutron beam and proton target were alternately polarized for the measurements of A n and A p . A mirror-symmetric detection system was used to cancel geometry-related systematic errors. From fits of the measured asymmetry angular distributions over the range of 53.4°р cm р86.9°, the difference in the zero-crossing angles of the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 47 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…Extensive experimental searches for charge symmetry violation effects have shown that charge symmetry holds to the order of the protonneutron mass difference [5,6].…”
Section: Is Reduced Tomentioning
confidence: 99%
“…Extensive experimental searches for charge symmetry violation effects have shown that charge symmetry holds to the order of the protonneutron mass difference [5,6].…”
Section: Is Reduced Tomentioning
confidence: 99%
“…Extensive experimental searches for charge symmetry violation effects have shown that charge symmetry holds to the order of the protonneutron mass difference [5,6]. 5 Therefore, charge symmetry can not explain the discrepancy between the NMC measurement and the traditional Gottfried Sum result.…”
Section: Is Reduced Tomentioning
confidence: 99%
“…Charge symmetry breaking (CSB) in neutron-proton elastic scattering manifests itself as a non-zero difference of the neutron (A n ) and proton (A p ) analyzing powers, ∆A = A n −A p = 2×[Re(b * f )+Im(c * h)]/σ 0 . The three precision experiments performed (at TRIUMF at 477 MeV [12] and at 369 MeV [13], and at IUCF at 183 MeV [14]) have unquestionably shown that charge symmetry is broken and that the results for ∆A at the zero-crossing angle of the average analyzing power, are very well reproduced by meson exchange model calculations (see Fig.1). As shown above a T-odd / P-even interaction corresponds to a term in the scattering amplitude which is simultaneously charge symmetry breaking.…”
Section: Nucleon-nucleon Interactionmentioning
confidence: 84%